The Decline and Potential Collapse of Federal Guideline Sentencing - David Robinson Jr. (Washington University Law Quarterly, 1996)
Although it represents an impressive intellectual effort, the present federal sentencing structure is markedly dysfunctional in practice. A recent directive by the Attorney General, to all federal prosecutors, makes an already deeply flawed system so unjust that it deserves speedy replacement. This Article begins by discussing the nature of the problem. Then, the Article discusses the problem's recent history regarding the scope of prosecutive discretion, both traditionally and under the Sentencing Reform Act and Guidelines, and the efforts to reduce the effect of prosecutive discretion. It concludes with a consideration of what is to be done to rectify the problem.
Keywords: Sentences (Criminal procedure); Prosecution – Decision making